Complete genome sequence analysis of novel human bocavirus reveals genetic recombination between human bocavirus 2 and human bocavirus 4 - Pattara Khamrin (2018)
Epidemiological surveillance of human bocavirus (HBoV) was conducted on fecal specimens collected from hospitalized children with diarrhea in Chiang Mai, Thailand in 2011. By partial sequence analysis of VP1 gene, an unusual strain of HBoV (CMH-S011-11), was initially identified as HBoV4. The complete genome sequence of CMH-S011-11 was performed and analyzed further to clarify whether it was a recombinant strain or a new HBoV variant. Analysis of complete genome sequence revealed that the coding sequence starting from NS1, NP1 to VP1/VP2 was 4795 nucleotides long. Interestingly, the nucleotide sequence of NS1 gene of CMH-S011-11 was most closely related to the HBoV2 reference strains detected in Pakistan, which contradicted to the initial genotyping result of the partial VP1 region in the previous study. In addition, comparison of NP1 nucleotide sequence of CMH-S011-11 with those of other HBoV1-4 reference strains also revealed a high level of sequence identity with HBoV2. On the other hand, nucleotide sequence of VP1/VP2 gene of CMH-S011-11 was most closely related to those of HBoV4 reference strains detected in Nigeria. The overall full-length sequence analysis revealed that this CMH-S011-11 was grouped within HBoV4 species, but located in a separate branch from other HBoV4 prototype strains. Recombination analysis revealed that CMH-S011-11 was the result of recombination between HBoV2 and HBoV4 strains with the break point located near the start codon of VP2. © 2013 Elsevier B.V.